2012
DOI: 10.3892/or.2012.1703
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cav-1 in tumour cells, rather than in stromal tissue, may promote cervical squamous cell carcinoma proliferation, and correlates with high-risk HPV infection

Abstract: Abstract. Altered expression of caveolin-1 (Cav-1) is observed in various types of cancers. However, little research has been reported regarding the correlation between the expression of Cav-1 and cervical cancer. Here, we investigated the clinical significance of Cav-1 expression using quantum dot (QD)-based immunofluorescence staining in cervical cancer and its correlation with high-risk human papilloma virus (HPV) infection detected by chromogenic in situ hybridization. Our results showed that the positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In our study, to ensure that our results were comparable with those of the other labs, we examined the status of Cav-1 and LC3B using the developed QDs-IHC method that was well-established and widely used in quantitative and semiquantitative studies [23,4345] rather than using the developing QDs-based multiplexed molecular imaging technology. Furthermore, results from Yan Li and colleagues [40] and the current study showed that QDs-based multiplexed molecular imaging is highly suitable for observing the heterogeneity of cancer cells and stromal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, to ensure that our results were comparable with those of the other labs, we examined the status of Cav-1 and LC3B using the developed QDs-IHC method that was well-established and widely used in quantitative and semiquantitative studies [23,4345] rather than using the developing QDs-based multiplexed molecular imaging technology. Furthermore, results from Yan Li and colleagues [40] and the current study showed that QDs-based multiplexed molecular imaging is highly suitable for observing the heterogeneity of cancer cells and stromal cells.…”
Section: Resultsmentioning
confidence: 99%
“…Every step followed the manufacturer’s instructions (Wuhan Jiayuan Quantum Dots Co., Ltd., Wuhan, China) and was the same as indicated in our previous study [45] with the following major steps: deparaffinizing→antigen retrieval→blocking→primary antibodies for Cav-1 and LC3B→washing→biotinylated goat anti-rabbit IgG (for Cav-1)→washing and blocking→605-QD-SA washing and QDs (545 nm) conjugated to goat anti-murine IgG (1:100, Wuhan Jiayuan Quantum Dots Co., Ltd, Wuhan China)→washing→mounting and observation. The QD fluorescent signal was analyzed using the Caliper multispectral microscopy imaging system (Caliper Life Sciences, Hopkinton, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…– CAV1 expression in tumor cells may contribute to cell proliferation and was associated with positive HPV‐infection…”
Section: Introductionmentioning
confidence: 99%
“…At present, the role of Cav-1 in the stromal microenvironment remains unknown. 18 Therefore, further studies are needed to discover the functions of stromal Cav-1 in cervical SCC.…”
Section: The Different Functions Of Cav-1 In Sccsmentioning
confidence: 99%
“… 12 These evidences indicate that Cav-1 may regard as a tumor suppressor. In contrast, the expression of Cav-1 was reported to increase in prostate cancer, 13 bladder cancer, 14 renal cancer 15 and esophageal SCC, 4 , 16 head and neck SCC (HNSCC), 17 cervical SCC 18 and tongue SCC. 19 Interestingly, these upregulations have also been associated with advanced tumor stage, lymph node metastasis and poor prognosis of cancer patients, which may imply that Cav-1 can function as a tumor promoter.…”
Section: Introductionmentioning
confidence: 99%